The young people of Mali: Key players against COVID-19 - United Nations Interregional Crime; Justice Research Institute (Freedom from Fear, 2020)
The world is shaken by an unprecedented health crisis. Its multiple ravages are echoing all over the world and the media seem to revel in it as information concerning the situation becomes vital. Needless to say, Covid-19 made its appearance at the end of 2019 in Wuhan, the capital of the province of Hubei in China, and at the start of 2020, continued to spread in an overpowering and dominant way, not only characterized by its speed but also in its capacity of adaptation across all continents of the world. China has been overwhelmed. In France, there are no longer yellow vest protests. Italy no longer sings and the art world present in the country has closed its doors. It would seem that America, in tears, suddenly forgot its superpower. The virus rapidly spread also in Latin America, with more than 11 thousand cases in 24 hours in Brazil. All of this to show the very serious impact that Covid-19 has provoked on daily life around the world. In fact, on March 11, it qualified as a pandemic by the World Health Organization (WHO), exceeding the number of 100 infected countries to all areas of the globe.